Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.4097/kja.20640
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous dexamethasone on the duration of postoperative analgesia for popliteal sciatic nerve block: a randomized, double-blind, placebo-controlled study

Abstract: BackgroundIntravenous (IV) dexamethasone prolongs the duration of a peripheral nerve block; however, there is little available information about its optimal effective dose. This study aimed to evaluate the effects of three different doses of IV dexamethasone on the duration of postoperative analgesia to determine the optimal effective dose for a sciatic nerve block.MethodsPatients scheduled for foot and ankle surgery were randomly assigned to receive normal saline or IV dexamethasone (2.5 mg, 5 mg, or 10 mg). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…In recent published meta-analysis, only 10 mg of IV dexamethasone significantly prolonged analgesic duration of peripheral nerve blocks not 4 and 8 mg [27]. The same results were also shown in the recently published RCT according to dexamethasone dose in the sciatic nerve block [28]. High dose of dexamethasone may cause hyperglycemia, but the increase of blood glucose level was not significant in this study.…”
Section: Discussionsupporting
confidence: 84%
“…In recent published meta-analysis, only 10 mg of IV dexamethasone significantly prolonged analgesic duration of peripheral nerve blocks not 4 and 8 mg [27]. The same results were also shown in the recently published RCT according to dexamethasone dose in the sciatic nerve block [28]. High dose of dexamethasone may cause hyperglycemia, but the increase of blood glucose level was not significant in this study.…”
Section: Discussionsupporting
confidence: 84%
“…Previous research has demonstrated the efficacy of intravenous injection of glucocorticoids in preventing PONV. 35 Kim et al reported no significant difference in the incidence of nausea and vomiting after sciatic nerve block between intravenous dexamethasone 2.5, 5, 10 mg, and placebo, 13 which is consistent with our results.…”
Section: The Mechanisms Of Betamethasone To Prolong Postoperative Ana...supporting
confidence: 92%
“…Among these, long‐acting glucocorticoids have shown exciting results in extending the duration of FNB. When combined with the local anesthetic ropivacaine, dexamethasone prolongs the duration of analgesia after interscalene brachial plexus blocks, sciatic nerve blocks, and popliteal nerve blocks 13–16 . In this study, betamethasone, a long‐acting corticosteroid and stereoisomer of dexamethasone, was used instead of the commonly employed dexamethasone.…”
Section: Introductionmentioning
confidence: 99%
“…All nerve blocks were performed under ultrasound guidance by the same physician, skilled in nerve block techniques, which could ensure the effectiveness of the nerve block, and patients were excluded from this study if they had significant pain (NRS≥3) three hours after surgery. At present, there is no optimal dose of intravenous dexamethasone for nerve block, and this study is based on the results of Kim et al 15 …”
Section: Discussionmentioning
confidence: 99%